Feasibility of Induction Docetaxel, Cisplatin, 5-Fluorouracil, Cetuximab (TPF-C) Followed by Concurrent Cetuximab Radiotherapy for Locally Advanced Head and Neck Squamous Cell Carcinoma - Charalambakis, Nikolaos; Kouloulias, Vassilis; Vaja, Helena; Pectasides, Dimitrios; Rampias, Theodoros; Economopoulos, Theofanis; Katsaounis, Panagiotis; Siolos, Spiros; Bartzi, Valentina; Perisanidis, Christos; Laschos, Konstantinos; Maragoudakis, Pavlos; et al. (Frontiers in Oncology, 2013)
Purpose: To report our experience with a sequential regimen of induction TPF-C followed by radioimmunotherapy with cetuximab in patients with locally advanced head and neck squamous cell carcinoma (HNSCC). Patients and Methods: Toxicity and outcome was retrospectively analyzed in 22 patients receiving sequential therapy with induction TPF-C followed by radioimmunotherapy between October 2008 and December 2011. Outcome was estimated using Kaplan–Meier analyses. In addition, we performed mutation analysis for PIK3CA genes and high risk HPV DNA detection using PCR. Results: Mean time of follow-up was 16 months. Six patients were TNM Stage III, 15 patients IV (IVA or IVB), and one patient Stage II with bulky disease. During TPF-C, Grade 3 and 4 toxicities occurred in eight patients, dose modifications in seven, delays in one, and unplanned admissions in five. Clinical tumor response was documented in 18 of the 21 patients who completed at least three cycles of TPF-C with three patients developing complete response and 15 partial responses. Grade 3/4 mucositis was observed in six patients. At a median follow-up of 19 months, 13 patients were alive and nine had died including seven patients as a result of disease persistence or recurrence and two as a result of unrelated causes. PIK3CA mutations were not identified and our two oropharynx cases were HPV negative. Conclusion: The combination of induction TPF-C with concurrent cetuximab radioimmunotherapy in patients with locally advanced HNSCC is tolerable, with encouraging efficacy.